ANALISIS PENGARUH KONDISI MAKRO EKONOMI TERHADAP KONSUMSI JASA ASURANSI UMUM DI INDONESIA - Agustian Kuswari; Muhammad Komri Yusuf; Enny Muhaini Hanafiah (Department of Development Economics, Universitas Sriwijaya, 2005)
The objective of this research are, 1) To analyze characteristic relation of condition macroeconomic on gross premium of general insurance in Indonesia. 2) To analyze the influence of condition of macroeconomic on gross premium of general insurance in Indonesia, with used linier simple regression and linier multiple regression model. The find result of this study as follow, 1) Generally, condition of macroeconomic have positive influnce on gross premium of general insurance in Indonesia. 2) Generally, condition of macroeconomc have strong and significant influence on gross premium of general insurance in Indonesia.Keywords: Gross Premium, General Insurance